1999
DOI: 10.2519/jospt.1999.29.7.413
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Properties of Thera-Band® Tubing During Shoulder Abduction Exercise

Abstract: Kenneth Hurd, DP7; MS, ATC2 Allan )ones, DPP Stephen Sprigle, PhDStudy Design: Single-group, repeated measures. Objectives: To investigate the relationship between tubing length and tubing tension for 6 colors of Thera-Band tubing (each color representing a different level of resistance) and to estimate the resistive shoulder toque provided during shoulder abduction exercise. Background: Thera-Band tubing is popular for providing resistance in rehabilitation strengthening programs. Unfortunately, it is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 16 publications
2
40
3
3
Order By: Relevance
“…the increase in length corresponded to a progressive increase in the elastic resistance and stiffness of the material in the color sequence: tan, yellow, red, green, blue, black, silver and gold. Furthermore, the results showed a mean value of r 2 equal to 0.95, in agreement with Hughes et al 2 and Page, Labbe and Topp 10 who also found a linear force-deformation relationship with mean values of r 2 of 0.93 and 0.97, respectively. In this linear behavior, there was a 53.8% variation from the least resistant band (tan) to the most resistant band (gold).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…the increase in length corresponded to a progressive increase in the elastic resistance and stiffness of the material in the color sequence: tan, yellow, red, green, blue, black, silver and gold. Furthermore, the results showed a mean value of r 2 equal to 0.95, in agreement with Hughes et al 2 and Page, Labbe and Topp 10 who also found a linear force-deformation relationship with mean values of r 2 of 0.93 and 0.97, respectively. In this linear behavior, there was a 53.8% variation from the least resistant band (tan) to the most resistant band (gold).…”
Section: Discussionsupporting
confidence: 80%
“…Resistive elastic materials, such as bands and tubes, are low-cost and highly versatile tools often used in therapeutic exercise programs [1][2][3] . They are also convenient for patients to train at home using a variety of movement, including eccentric and concentric contractions 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In general, no appreciable differences in tension were found between Cando and Thera-Band brands of tubing of the same color except for the yellow and grey tubings. For these colors, performing the same exercise with Thera-Band tubing will lead to less resistance than using tubing made by Cando.…”
Section: Discussionmentioning
confidence: 99%
“…In Pilates, exercise is performed on the Reformer apparatus, with the individual positioned in supine position with feet supported on a bar; this horizontal position reduces the action of gravity (13), being commonly used when the injured joint is not able to support the entire body weight (14). External overload occurs by the use of springs, through which the change in length (applied force), the type of material (elasticity modulus), and the cross section dictate the strength magnitude and the value of the stored potential energy (15). In this exercise, the spring is stretched during the knee extension movement, generating a gradual increase in resistance, and progressively decreases during the movement return in knee lexion.…”
Section: Introductionmentioning
confidence: 99%